Temperature and pressure effects on the partitioning of V and Sc between clinopyroxene and silicate melt; implications for mantle oxygen fugacity - Li Yuan, Li Yuan (The American mineralogist, 2018)
The partition coefficients of V and Sc between clinopyroxene and silicate melt (DVCpx/SM and DScCpx/SM) have been determined experimentally at 1200-1400 °C and 0.8-2.3 GPa, using a hornblende- and clinopyroxene-rich mantle rock in graphite-lined Pt95Rh05 capsules. The results show that the DVCpx/SM and DScCpx/SM values decrease from 3.8 to 2.3 and from 2.6 to 1.1, respectively, as the experimental temperature and pressure vary from 1200 °C and 0.8 GPa to 1400 °C and 2.3 GPa. The presence of water in silicate melts may also reduce DVCpx/SM and DScCpx/SM. These results imply that the effects of temperature, pressure, and melt water content on DVCpx/SM should be considered when using V systematics in cratonic mantle peridotites to constrain cratonic mantle oxygen fugacity (fO2). However, although the dominant V in the present silicate melt is mixed V3+ and V4+, the DVCpx/SM/DScCpx/SM together with literature data obtained at similar fO2 shows a nearly constant value of 1.68 ± 0.26, regardless of temperature, pressure, melt composition, and melt water content, indicating that these factors cannot cause fractionation of Sc3+ from mixed V3+ and V4+ in mantle melts through clinopyroxene/silicate melt partitioning. Therefore, in combination with V/Sc systematics in primitive MORBs and arc basalts, using DVCpx/SM and DScCpx/SM obtained at 1 bar and dry conditions should be valid to constrain mantle fO2, except for the case that the DCpx/SM for Sc3+ can be demonstrated to be fractionated from the DCpx/SM for mixed V4+ and V5+, which are present in oxidized basalts.